ANALISIS PERBANDINGAN CUKO PEMPEK DARI ASAM LAKTAT DAN YAKULT - Wahyono, Lilik; Muchsiri, Mukhtarudin; Yani, Ade Vera (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2013)
The objective of this research to determine the optimally concentration of lactic acid and yakult to make cuko pempek. This research has done in the laboratory Agriculture Faculty of Muhammadiyah University Palembang it started from December 2012 to April 2013. This research used Completely Randomized Design (CRD) are arranged in Factorial which consists of six unit experiments were repeated three times for each treatment is A1 (lactic acid 200 ml concentration), A2 (lactic acid 250 ml concentration), A3 (lactic acid 300 ml concentration), A4 (yakult 200 ml concentration), A5 (yakult 250 ml concentration), and the treatment of A6 (yakult 300 ml concentration). The observed Parameters in this research was chemical analysis which consists of acid total, acidity (pH), sugars total, viscosity and lactid acid bacterium (BAL) viability. The organoleptic test of cuko pempek consists of color, flavor, and taste. The results showed that the coparation of of lactic acid concentration and yakult has very significant effect of acid total, acidity (pH), sugars total, viscosity and lactid acid bacterium (BAL) viability. The organoleptic test of the comparation from lactid acid and yakult of cuko pempek taste showed that A6 unit experiment for taste has very different significant effect with cuko pempek generally. The research conclusion showed that C6 unit experiment has the best cuko pempek with acid total (0.66%), acidity /pH (6.13), sugar total (28.97% brix), viscosity (1.31 cP), lactid acid bacterium (BAL) viability (5.6 E +04 CFU / ml of colony), color, flafor, and taste whit has grade three.